The prospects of international trade regulation : from fragmentation to coherence - Cottier, Thomas; Delimatsis, Panagiotis (Cambridge : Cambridge University Press, 2011)
'For a long time, the GATT led a life of its own as a self-contained regime. The evolution from tariff to non-tariff barriers brought about increasing overlaps with other regulatory areas. WTO rules increasingly interface with other areas of law and policy, including environmental protection, agricultural policies, labour standards, investment, human rights and regional integration. Against this backdrop, this book examines fragmentation in international trade regulation across a wide array of regulatory fields. To this end, it uses a conceptually coherent theoretical framework which is based on the effort to bring about greater coherence among different policy goals and fields, and thus to embed the multilateral trading system within the broader framework of international economics, law and relations. It will appeal to those interested in a forward-looking discussion of the most pressing issues of the international trade agenda'--
Machine generated contents note: 1. The fragmentation versus coherence discourse in international law and its relevance for trade regulation Thomas Cottier, Panagiotis Delimatsis and Katja Gehne; Part I. Constitutional Issues in International Trade Regulation: 2. The constitutionalisation of international trade law Klaus Armingeon, Karolina Milewicz, Simone Peter and Anne Peters; 3. Reflections on modes of decision-making in the WTO Yves Bonzon, Manfred Elsig, Marina Foltea, Thomas Messerli and Andreas Ziegler; 4. Regionalism - moving from fragmentation towards coherence Richard Baldwin and Theresa Carpenter; Part II. Reforming Specific Areas of Trade Regulation: 5. Reframing sustainable agriculture Philipp Aerni, Baris Karapinar and Christian Ha;berli; 6. Energy in WTO law and policy Thomas Cottier, Garba Malumfashi, Sofya Matteotti-Berkutova, Olga Nartova, Jo$1#0<(Ble De Se;pibus and Sadeq Z. Bigdeli; 7. Developing trade rules for services: a case of fragmented coherence? Panagiotis Delimatsis, Nicolas Diebold, Marti;n Molinuevo, Marion Panizzon and Pierre Sauve;; 8. Challenges of biotechnology in international trade regulation Susette Biber-Klemm, Michael Burkard, Thomas Cottier, Sufian Jusoh and Michelangelo Temmerman; Part III.'Trade and ...' Linkages: 9. A call for a WTO ministerial decision on trade and human rights Barnali Choudhury, Katja Gehne, Simone Heri, Franziska Humbert, Christine Kaufmann and Krista Nadakavukaren Schefer; 10. The protection and promotion of cultural diversity in a digital networked environment - mapping possible advances to coherence Mira Burri, Christoph Beat Graber and Thomas Steiner; 11. Development and stability in the nexus between trade and finance Ernst Baltensperger and Nils Herger; 12. International investment framework - the regulatory fragmentation challenge in a changing world economy Bertram Boie, Julien Chaisse and Philippe Gugler; 13. Low-income countries and commodity price volatility Hannah Bargawi, Elva Bova, Benno Ferrarini and Susan Newman.s
Includes bibliographical references and index.
Keywords: Foreign trade regulation